PENDAMPINGAN PEMASARAN PRODUK DAN PELATIHAN PENYUSUNAN PEMBUKUAN PADA KELOMPOK PEMBUAT MINYAK TANUSAN DI DESA DUDA TIMUR KECAMATAN SELAT KARANGASEM - NI KOMANG SUMADI; NI LUH ADISTI ABIYOGA WULANDARI; I WAYAN SUDIANA; SANG AYU PUTU ARIE NDRASWARAWATI; NI PUTU AYU KUSUMAWATI; COKORDA BAYU PUTRA (JURNAL SEWAKA BHAKTI, 2019)
The Karangasem Strait sub-district, precisely in Duda Timur Village, is a sub-district seen from the perspective of its livelihood, with the majority of the population working as farmers. The majority of the plantation products are salak and head. Aside from being a farmer, some households use their plantation products as business land to be able to supplement their income, one of which is to use coconuts produced from plantations as Tanusan Oil. Tanusan oil is one of the traditionally made oils. This tanusan oil is still in great demand by the people in Bali because by cooking using tanusan oil the cuisine becomes more delicious and tasty. The business of the tanusan oil maker group still has not applied marketing management in its business processes so that the marketing method is only done by entrusting the products produced in stalls and according to order and so the bookkeeping has not been implemented in running its business so that it cannot know exactly how advantages and disadvantages clearly obtained. To help overcome these problems, we provide assistance in the field of marketing and simple bookkeeping so that in the future continuity of business can compete in the future. The results achieved in this community service are that this group of tanusan oil makers has been able to recommend its products to a wider market share and has been able to also do bookkeeping in a simple way.